Analisis Kualitas Website Sekolah Tinggi Teknologi Pekanbaru dengan Metode Webqual 4.0 dan IPA - Nadiah Nauroh Sabila (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2023)
The profile website has now been widely used, one of which is by the educational institution STT Pekanbaru. However, in the implementation of the website, there are still some obstacles, such as the appearance of the website that is less trendy and unattractive, navigation menus that cannot work, pages that cannot be accessed or errors, the information available is not detailed and not up to date, and there is no community space and suggestion box. Therefore, the purpose of this study is to analyze website performance in terms of user responses so that in the future improvements can be made that can improve the quality of service and website quality. The solution uses Webqual 4.0 and Importance Performance Analysis (IPA) methods. The respondents who were sampled were 96 people and used accidental sampling techniques. The data will be processed by utilizing Ms Excel and SPSS 25. The results obtained stated that the Pekanbaru STT website has a conformity rate of 87% or <100% with an average gap value (GAP) of -0.49. Meanwhile, the results of the IPA quadrant analysis are monitored there are 5 attributes which are the top priority so that they can get improvement. And the CSI calculation results get a value of 79.70%, which is in the 2nd category which means